Breast cancer mortality: characterization and trend line in northeastern Brazil - Pereira, Leonilson da Silva (2020)
The objective of the present study was to analyze the growth of breast cancer mortality in the northeast region of Brazil, using a descriptive ecological time series method, which was conducted by collecting secondary data on breast cancer death rates in northeast Brazil. Brazil. With information on deaths from breast cancer obtained from the mortality information system (SIM) of the Ministry of Health (MS), in accordance with the International Classification of Diseases (ICD). The population sense was obtained from the Brazilian Institute of Geography and Statistics (IBGE), through the IBGE Automatic Recovery System (SIDRA). Bibliographic analysis was performed and we defined the following criteria to analyze: year of notification, interval from 2007 to 2016, region of notification and age. With regard to results the data show that there is a linearly increasing trend in the mortality rate of women due to breast cancer mainly over the years. Among the conclusions, risk factors such as genetics, lifestyle, time, age, disinformation, regions, as well as patient neglect and government neglect of both the quality of public health and the scarcity of preventive programs, provide and corroborate. for the aggravation of the deaths of this pathology.